Oral Potentially Malignant Disorders: A Comprehensive Review of Diagnostic Approaches and Management Strategies - Angabeen Anjum; Nauman Sheikh (Journal of Bahria University Medical and Dental College, 2024)
Oral potentially malignant disorders (OPMDs) encompass a group of conditions that have an increased risk of progressing to oral cancer. Timely diagnosis and effective management of these disorders play a crucial role in preventing malignant transformation and improving patient outcomes. This review article provides a comprehensive overview of the diagnostic approaches and management strategies for OPMDs. It discusses the current understanding of OPMDs, highlights the various diagnostic methods available, and explores the evolving landscape of management options. The aim of this review is to enhance the knowledge and awareness of healthcare professionals involved in oral pathology and promote effective decisionmaking in the diagnosis and management of OPMDs.